2012
DOI: 10.15230/scsk.2012.38.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Protective Effect and Liposome Formulation for Enhanced Transdermal Delivery of Isoquercitrin

Abstract: In this study, the cellular protective effect of isoquercitrin against H2O2 and rose bengal-indued HaCaT cell damage was investigated. The ethosome and elastic liposome for enhanced transdermal delivery were prepared. Particle size, loading efficiency and cumulative permeated amounts of them were evaluated. Isoquercitrin didn't show any characteristic cytotoxicity at 50 µM. When HaCaT cells were treated with 5 mM H2O2 and 25 µM rose bengal, isoquercitrin protected the cells against the oxidative damage in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Isoquercitrin is the glycoside of quercetin, a type of polyphenol, and is known to have various medical effects such as antioxidant, anti-inflammation, anti-allergy, anti-cancer, hypertension and hyperlipidemia inhibition effects [27]. In the research of Jo [28], it was proved that isoquercitrin has an excellent cell protective effect by increasing the survival rate of the oxidative damage induced HaCaT cells, and the feasibility of isoquercitrin to skin aging by active oxygen was suggested. In this research, it was found that EF breaks down proteins such as collagen and reduces the expression of MMP-9 mRNA which fosters aging.…”
Section: Discussionmentioning
confidence: 99%
“…Isoquercitrin is the glycoside of quercetin, a type of polyphenol, and is known to have various medical effects such as antioxidant, anti-inflammation, anti-allergy, anti-cancer, hypertension and hyperlipidemia inhibition effects [27]. In the research of Jo [28], it was proved that isoquercitrin has an excellent cell protective effect by increasing the survival rate of the oxidative damage induced HaCaT cells, and the feasibility of isoquercitrin to skin aging by active oxygen was suggested. In this research, it was found that EF breaks down proteins such as collagen and reduces the expression of MMP-9 mRNA which fosters aging.…”
Section: Discussionmentioning
confidence: 99%
“…또한 ROS는 피부 기저막에 있는 멜라닌세포의 활성화를 통하여 멜라닌세 포 증식 및 멜라닌 합성을 증가시킨다고 보고되고 있다 [4][5][6][7][8]. 따라서 활성산소를 효율적으로 제거하고 세포 및 조직을 보호하기 위해서는 피부 항산화 방어망 구축 및 항산화 효능이 큰 항산화제의 개발이 절 실히 요구되고 있는 실정이다 [9,10].…”
unclassified
“…Keywords: Glycyrrhiza uralensis, Glycyrrhiza glabra, DPPH assay, luminol chemiluminescence assay, cellular protective effect [4][5][6][7].…”
mentioning
confidence: 99%